Dendritic unzipped carbon nanofibers enable uniform loading of surfactant-free Pd nanoparticles for the electroanalysis of small biomolecules. Issue 12 (6th March 2017) - Zhang, Yan; Li, Mengpei; Chen, Qidi; Cai, Daoping; Zhan, Hongbing
Abstract : Illustration of the mechanisms of SCNF and preparation of Pd/GNF composites and Pd/GNF sensors for the simultaneous determination of small biomolecules. Abstract : In this study, graphene nanofibers (GNF), which are a superior support material, are successfully synthesized via the dendritic unzipping of stacked-cup carbon nanofibers (SCNF). Ultrasmall Pd nanoparticles are uniformly dispersed on the GNF (Pd/GNF) via chemical reduction under mild conditions without any surfactant involved. The components and structure of Pd/GNF are evaluated via scanning electron microscopy (SEM), transmission electron microscopy (TEM), powder X-ray diffraction (XRD), Raman spectra and X-ray photoelectron spectroscopy (XPS). The characterization results indicate that the Pd nanoparticles have a uniform size of 3–6 nm without significant aggregation and the overall Pd content is about 11.2 wt% in the Pd/GNF composite. Moreover, a modified electrochemical sensor based on the Pd/GNF composite is successfully fabricated. In the two investigated redox probes (IrCl6 2− and [Fe(CN)6 ] 3− ), Pd/GNF shows a superior electrochemical response compared to the Pd nanoparticles loaded on SCNF and bare glass carbon electrode. For the detection of small biomolecules, Pd/GNF could individually or simultaneously detect ascorbic acid (AA), dopamine (DA) and uric acid (UA) through differential pulse voltammetry. The linear concentration ranges of UA, DA and AA are 0.1–1200 μM, 1–180 μM and 0.1–6000 μM, respectively.